Implementation of Learning Using Interactive Multimedia Based on Android On Theme 9 be Class V SD - Inge Kadarsih; Yanti Fitria (Jurnal Ilmiah Sekolah Dasar, 2022)
The problem in the thematic learning of class V Elementary School is caused by conventional teaching methods and does not use engaging learning media so that students feel bored to take part in learning activities. This research is a follow-up to the results of the validity test and practicality test of interactive multimedia developed using the Android Operating System. This study aims to analyze the effectiveness of android-based interactive multimedia. The method used to collect data is observation, interviews, and tests. The instrument used to collect data is a test question. Data were analyzed using a t-test. In previous studies, the validity of android-based interactive multimedia was tested through expert validity tests and practicality tests through individual trials. The effectiveness of using Android-based interactive multimedia was tested by giving a pretest-posttest in the form of an objective test consisting of 20 questions with 12 students. The effectiveness test results of student learning outcomes from the pretest and post-test data showed an increase from the average before using android-based interactive learning media. Based on these data, it can be said that interactive multimedia based on android thematic learning to improve student learning outcomes in students is valid, practical and effective for use in the learning process. Thus, it can be said that the Android-based interactive multimedia developed effectively improves the learning outcomes of fifth-grade elementary school students.